116k views
3 votes
PLEASE HELP FAST!!!

Simplify the expression.
(x + 6)^2

Please don’t guess I really need to get this problem correct. My grade depends on it!

User Jason Song
by
5.5k points

2 Answers

5 votes

Answer:


\large\boxed{(x+6)^2=x^2+12x+36}

Explanation:


(x+6)^2\\\\\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\=x^2+2(x)(6)+6^2=x^2+12x+36\\\\\text{Other method}\\\\(x+6)^2=(x+6)(x+6)\\\\\text{use FOIL:}\ (a+b)(c+d)=ac+ad+bc+bd\\\\=(x)(x)+(x)(6)+(6)(x)+(6)(6)=x^2+6x+6x+36\\\\=x&^2+12x+36

User Sorakthun Ly
by
6.0k points
1 vote

(a+b)²=a²+2ab+b²

(x+6)²=x²+2× x × 6+6²=x²+12x+36

hope this helps :)

User Fxtentacle
by
5.7k points